Quality education - Sharma, Shalender and Thakur, Saneel (Yojana)
The education system in India is transforming itself from focusing on universalisation of access to quality education , in line with the sustainable development goals, (SDG 4 in particular,). As per the national sample survey, the literacy rae of persons of age 7 years and above at the all-India level stood at 77.7 per cent. The 2030 agenda for sustainable development adopted by India in 2015 aims to (3z(Bensure inclusive and equitable quality education and promote lifelong learning opportunities for all(3y (Bby 2030: - Reproduced s